Enteng Kabisote Okay ka fairy ko... the legend - Reyes, Tony (Octo Arts, 2004)
Enteng Kabisote is tagalupa married to Faye, a lovely fairy and only daughter of Ina Magenta, Queen of Engkantasya, an enchanted kingdom. The couple has two kids Aiza and Benok - the family is living peacefully and happily until the day Satana, the evil queen of Kadiliman brings chaos to earth by sending Romero, Lucy and Fer to poison the water of the dams. But Venuz and Aries armor fairies sent by Ina Magenta stopped them.